ANALISIS TINGKAT KETAHANAN PANGAN TERHADAP KERAWANAN PANGAN MENGGUNAKAN METODE GIS (Geographic Information System) - Mulono Apriyanto; Rujiah Rujiah (Journal of Food System & Agribusiness, 2021)
The purpose of this study was to analyze the distribution of food security levels against food insecurity using the GIS (Geographic Information System) method. This research was conducted using a survey method during February and June 2019, located in Indragiri Hilir Regency. The data used are indicators of food security, indicators of food access and indicators of food utilization. In order to know the distribution of data resistance levels, it is analyzed using Geographical Information Systems (GIS). The results showed that the distribution of food security levels in the twenty sub-districts in Indragiri Hilir Regency had various conditions including food insecurity, somewhat food insecurity, sufficient food resistance, food resistance and very food resistance. % of stunted children and (%) the ratio of health workers are indicators that affect the level of food security and food insecurity. The study concluded that the distribution of food security levels among sub-districts in Indragiri Hilir Regency has conditions, among others, somewhat food insecurity, food resistance, sufficient food resistance and very food resistance. % of stunted children and (%) the ratio of health workers have an effect on the level of food insecurity as indicators of food security)